Peace, prosperity and pro-growth entrepreneurship - Wim Naudé (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Support for entrepreneurship is widely seen as a mechanism to facilitate prosperity and peace in a growing number of post-conflict states. In this paper I critically evaluate this view. I argue that entrepreneurship is a ubiquitous quality in post-conflict states but not necessarily always for the good. Unproductive and destructive entrepreneurship may inhibit the resurgence of the private sector and might even cause a relapse into conflict. To limit unproductive and destructive entrepreneurship there are at least six dimensions which need to be taken into consideration, namely: the context of war, the relationship between institutions and entrepreneurship, the role played by ethnic/immigrant (minority) entrepreneurs and entrepreneurs in diaspora, the scope of the market, human and financial capital requirements, and appropriate forms of government support. Further research on entrepreneurship in post-conflict states is needed to overcome the current lack of data, which constrains policy design.
Keywords: M13; O12; D21; L25; 330; entrepreneurship; peace; security; reconstruction; development; Entrepreneurship-Ansatz; Unternehmensgründung; Politischer Konflikt